Implementation of Social and Environmental Responsibility in Business Practices in Indonesia - Miskun, Miskun; Sodikin, Sodikin (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
Social and environmental responsibility is a vital aspect of sustainable business practices, where companies play a significant role in fostering social progress while also protecting the environment. In Indonesia, the importance of implementing social and environmental responsibility is becoming increasingly clear, spurred by rising public awareness and regulations that promote the active participation of the business sector in social and environmental initiatives. This article examines how social and environmental responsibility is integrated into Indonesian business practices by reviewing relevant legal foundations, such as Law Number 40 of 2007 concerning Limited Liability Companies. It also assesses how companies are executing social and environmental programs. The methodology used in this study is normative, focusing on the analysis of social and environmental responsibility as outlined in the Limited Liability Company Law. The findings indicate that, despite some progress, there are still challenges, including limited transparency, insufficient accountability, and inconsistencies in reporting. To strengthen social and environmental responsibility in sustainable development in Indonesia, greater collaboration is needed among the government, the business sector, and the community.